2011
DOI: 10.1063/1.3593496
|View full text |Cite
|
Sign up to set email alerts
|

Surface-electrode ion trap with integrated light source

Abstract: An atomic ion is trapped at the tip of a single-mode optical fiber in a cryogenic (8 K) surface-electrode ion trap. The fiber serves as an integrated source of laser light, which drives the quadrupole qubit transition of $^{88}$Sr$^+$. Through \emph{in situ} translation of the nodal point of the trapping field, the Gaussian beam profile of the fiber output is imaged, and the fiber-ion displacement, in units of the mode waist at the ion, is optimized to within $0.13\pm0.10$ of the mode center despite an initial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 19 publications
(18 reference statements)
1
40
0
Order By: Relevance
“…The second problem is that dielectric surfaces are susceptible to light-induced charging, which results in strong and difficult-to-control forces on the ions, inducing micromotion, large displacements, or even making the ions untrappable [79][80][81]. Nonetheless, these challenges have started to be addressed in the last several years by a number of groups integrating various optical elements with ion traps, including microfabricated phase Fresnel lenses [82,83], embedded micromirrors [84,85] and fibers [45,86], transparent trap electrodes [44], nanophotonic dielectric waveguides [87], macroscopic optical cavities [46,[88][89][90][91], and microscopic, fiber-based cavities [92].…”
Section: Incorporating Optical Componentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The second problem is that dielectric surfaces are susceptible to light-induced charging, which results in strong and difficult-to-control forces on the ions, inducing micromotion, large displacements, or even making the ions untrappable [79][80][81]. Nonetheless, these challenges have started to be addressed in the last several years by a number of groups integrating various optical elements with ion traps, including microfabricated phase Fresnel lenses [82,83], embedded micromirrors [84,85] and fibers [45,86], transparent trap electrodes [44], nanophotonic dielectric waveguides [87], macroscopic optical cavities [46,[88][89][90][91], and microscopic, fiber-based cavities [92].…”
Section: Incorporating Optical Componentsmentioning
confidence: 99%
“…Brady et al [95] created an ion trap chip incorporating an array of optical fibers and confirmed ion trapping and preliminary light detection with their system, establishing a proof of concept for a large fiber array trap architecture. Following this work on light collection, Kim et al [45] demonstrated light delivery through an integrated single-mode (SM) fiber.…”
Section: Laser Delivery Via Integrated Optical Fibermentioning
confidence: 99%
See 3 more Smart Citations